In Pursuit of Excellence: Analysing the Indispensable Nature of Conduct and Discipline of Nepali Army in UN Peace Support Missions - Thapa, Subash (Unity Journal, 2024)
Nepal is currently ranked 2nd among the Troop Contributing Countries (TCCs) in United Nations Peace Support Operations. In this context, this paper examines the contribution of the Nepali Army's military conduct and discipline to the effectiveness of UN Peace Support Missions. The theoretical foundations delve into pertinent theories, particularly emphasizing Kevin S. Donohue's concepts of Discipline A (voluntary, value-based Attitudes) and Discipline B (externally enforced Behavioral responses) within the military framework. Maintaining conduct and discipline in UN peace operations is essential for ensuring the credibility and legitimacy of these missions. Therefore, prior UN reports and the Secretary General's Special Bulletin from 2015 to 2022 are comparatively analyzed to reflect on occurrences of misconduct involving peacekeepers from TCCs. Likewise, a quantitative comparative analysis assesses the status of the Nepali Army in terms of military conduct analyzing the rate of allegations of misconducts against it. The study employs descriptive statistics to analyze the status of misconduct allegations including that of serious misconduct to advocate for a stronger integration of military conduct with UN peacekeeping mandates, aiming to enhance overall effectiveness and elevate ethical standards in international peace operations. The findings underscore Nepal's exemplary practices in fostering both Discipline B and Discipline A within its peacekeeping forces. The paper concludes by demonstrating the substantial positive impact of disciplined behaviour on mission outcomes